Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Un centre communautaire pour la vie : un concept de « santé de la population » pour l’an 2000 - Couture, Roger T. (Reflets, 1999)
D’après les études épidémiologiques du Centre de santé publique du district de Sudbury (1992), il est important que cette communauté, comme maintes autres, s’attaque aux nombreux problèmes avec des idées nouvelles et des moyens plus efficaces pour améliorer la santé et contrôler l’évolution toujours plus onéreuse des coûts de santé. Depuis quelques années, nous savons que les stratégies de promotion de la santé peuvent aider les communautés de plusieurs façons. Pourtant, la promotion de la santé se situe loin dans la liste des priorités derrière le curatif ou les soins de première ligne dans le domaine de la santé. Ce texte vise à faire connaître comment on pourrait doter ce domaine d’une approche plus équilibrée en intégrant la dimension de la promotion de la santé. Pour ce faire, nous présenterons les objectifs d’une recherche, les approches et le processus que nous avons mené. Deuxièmement, nous ferons un survol des définitions et des modèles existants de la « santé de la population » (well being ou wellness) afin d’en dégager un modèle. Troisièmement, nous discuterons des obstacles à l’atteinte de la santé d’une population ou d’une communauté, notamment celle de la région de Sudbury. Finalement, nous proposerons un modèle communautaire de promotion de la santé qui fait le pont entre le modèle de santé de la population retenue et la communauté de Sudbury.

« Dialogue santé » une consultation historique auprès des communautés francophones de l’Ontario - Dallaire, Hélène; Rail, Geneviève (Reflets, 1995)

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.